Post Repeat Lower Segment Caesarean Section Cervicovesical Fistula - Vidya A.Thobbi (Al Ameen Medical College, 2008)
A 35 year old female patient G2P1L1 with previous LSCS with 9 months amenorrhea with labor pains was admitted and caesarean section was done for cephalo - pelvic disproportion with foetal distress. Patient developed cervico-vesical fistula which was successfully repaired by total abdominal hysterectomy and fistula was repaired using peritoneal flap .